Drinking water quality from various sources in the Shevchenkivsky district of Kharkiv - Lisnyak, A. A.; Kulyk, M. I.; Torma, S. (Man and Environment. Issues of Neoecology, 2025)
Purpose. Assessment of drinking water quality from different sources (centralized, decentralized) in the Shevchenkivskyi district of Kharkiv. Methods. Field, analytical, statistical. Results. Representative samples were selected from various water supply sources: natural springs, wells, city water supply. Organoleptic properties, physicochemical parameters and toxicological indicators were determined. Based on the analysis of all these characteristics in accordance with the requirements of DSTU 4808, it was determined that samples of artesian water TM "Shestakivska" are characterized by an optimal neutral pH, low metal content, moderate hardness and do not exceed the regulatory values ​​for any indicator. Water samples from private wells in the Shevchenkivskyi district of Kharkiv have increased total hardness, mineralization and salinity, which indicates the need for additional purification from salts. Water from centralized water supply, in addition to high total hardness, was characterized by the highest content of chlorine, iron and copper. A study was conducted to improve the quality of tap water at home. In particular, the effects of boiling, settling, freezing and filtering water on reducing the content of total salts and improving organoleptic indicators were studied. Conclusions. Artesian water of the Shestakivska trademark has the 1st quality class based on full compliance with the standards. Tap and spring water is classified as the 2nd quality class due to excess hardness and increased mineralization. The lowest indicators were recorded in water from a private well, which is classified as the 3rd quality class due to a significant excess of the hardness standard. An effective household method of demineralization of water is freezing and filtration.